Esophagogastroduodenoscopy procedure using disposable endoscope to detect the cause of melena in a patient with COVID‐19. Issue 1 (29th October 2020) - Xu, Fenghua; Yang, Yunsheng; Ding, Zhen
Abstract : Watch a video of this article